“An Idea Born from Desperation”. The Role of the Uniate Movement in the Bulgarian National Revival - Popek, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2014)
The article describes problems connected with the idea of a cooperation between Orthodox Bulgarian population and the Catholic Church at the turn of 50s and 60s of 19th century. The Uniate Movement was founded by Dragan Tsankov, who started to propagate the idea of westernization of Bulgarians in the newspaper “Bălgariya” with the cooperation with the French missionaries from the Congregation of the Mission and the Polish emigrants from the Hôtel Lambert. The <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">milieu of Dragan Tsankov firstly supported the Union in Kukush in 1859 and one year later leaded to the nationwide Union. These events played an important role in history of the Bulgarian Revival and development of the Church Movement. It contributed to the emergence of the Bulgarian exarchate (1870), which was a decisive step for the Bulgarian fight for political rights in the Ottoman Empire.